Effect of 2-chloroethyl trimethyl ammonium chloride on the bulb growth of different cultivars of tulip (Tulipa gesnerana) - MUKHERJEE, D; VERMA, R R; SINGH, D; MANUJA, S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Palampur during 1995-96 and 1996-97 to study the effect of foliar sprays of 2- chloroethyl trimethyl ammonium chloride, after carrying out deflowering at the early stage of flower emergence on the production and development of bulbs and bulblets of 4 cultivars of tulip (Tulipa gesnerana L.). Treatment with 2-chloroethyl trimethyl ammonium chloride was found to be effective in increasing the production and sIze of bulbs and bulblets with 2-chloroethyl trimethyl ammonium chloride 1 000 ppm being the most effective treatment. This treatment has increased the bulb yield by 48.2%, bulb weight by 116.2%, bulb circurmfetence by 19 3%, bulblet production by 29.1 % and bulblet weight by 56.8% compared with the untreated plants.